1963
DOI: 10.1139/y63-072
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Saturated Fat in Rats Fed Rapeseed Oil

Abstract: The effects of increasing the saturated fatty acids in a dietary vegetable oil composed mostly of unsaturated fatty acids were studied in rats. A mixture of palm oil and Swedish rapeseed oil fed for 4 weeks as 20% of a purified diet promoted weight gains which exceeded those obtained with Polish rapeseed oil of a similar content of erucic acid, and altered the proportion of saturated fatty acids in the tissues to reflect that of the diet. When methyl esters of saturated fatty acids were added to Swedish rapese… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
1
1

Year Published

1971
1971
2008
2008

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 4 publications
1
18
1
1
Order By: Relevance
“…Skeletal muscle changes, however, were not improved, but the vacuolar changes of the heart were increased in severity. Earlier Beare et al [4] demonstrated favourable effects on growth and food intake of rats when erucic acid was supplemented with HPO.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Skeletal muscle changes, however, were not improved, but the vacuolar changes of the heart were increased in severity. Earlier Beare et al [4] demonstrated favourable effects on growth and food intake of rats when erucic acid was supplemented with HPO.…”
Section: Discussionmentioning
confidence: 95%
“…Earlier, erucic acid was also demonstrated as the cause of growth retardation of rats fed RSO [5]. While the evidences incriminating erucic acid as the cause of the nutritional and pathological effects of RSO seemed convincing enough, the deficiency of saturated fatty acids in RSO appeared to be also contributing to its poor nutritional characteristics [4], The present study comprises 2 experiments which were concerned with the effects of oils and fats of various fatty acid compositions on the nutri tional and pathogenic characteristics of RSO in ducks.…”
Section: Introductionmentioning
confidence: 99%
“…The need for these changes came as a result of the extensive studies on the nutritional aspects of rapeseed. Enicic acid contained in rapeseed oil may cause hean, adrenal and ovarian tissue lesions in rats (Carroll and Noble, 1957;Beare et al, 1963). This led to the first development of low-enicic-acid rapeseed (LEAR) varieties that reduced emcic acid content from about 40% to 5%.…”
Section: Rapeseed and Its Utilizationmentioning
confidence: 99%
“…They are the major very long chain fatty acids (VLCFAs) in the seed oil, together accounting for 45-60% of the total fatty acid mixture. High levels of erucic acid in cooking and salad oil extracted from rapeseed have been associated with health problems (Beare et al 1963). Following identiWcation of a spontaneous rapeseed mutant with low erucic acid content, genetic studies have shown that this trait is under control of two loci that act in an additive manner (Harvey and Downey 1964;Kondra and Stefansson 1965).…”
Section: Introductionmentioning
confidence: 99%